A gestão participativa do desenvolvimento rural sustentável: o PRONAF na Subzona de Touros/ RN - Freitas, Dione Maria de (2008)
To investigate the possibilities and limits of mechanisms of participativa management in the scope of the Pronaf - National Program of Fortalecimento of Familiar Agriculture, and the corresponding effectiveness of its actions in the construction of alternatives of sustainable agricultural development in the Coast North of the State of the Great River of the North, more specifically, in the composed Subzona de Touros for the cities of Bulls, White Well, Pureness, Is Miguel of the Gostoso and Taipu. To carry through this analysis they had been carried through Research of Field with the objective to reconstitute the trajectory of the CMDRS, to trace the profile of the citizens that compose each one of the five advice, its expectations, interests and the level of participation of the local population